2020
DOI: 10.5114/fmpcr.2019.90163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of counselling based on the PLISSIT model on pregnant women’s sexual satisfaction: a randomised controlled trial

Abstract: Background. Sexual satisfaction is often reduced during pregnancy owing to some sexual problems. Sexual counselling offered for pregnant women may reduce the complications of this disorder during pregnancy. Objectives. This study was conducted to evaluate the effect of PLISSIT (permission, limited information, specific suggestions, and intensive therapy) model-based sexual counselling on pregnant women's sexual satisfaction. Material and methods. In this randomised controlled clinical trial, the effect of PLIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since there are not enough studies investigating the effect of counseling based on the Ex-PLISSIT model on primigravidas, it may be recommended to increase studies on this subject. Counseling based on the PLISSIT model, which is a similar model in pregnant women, was effective in improving sexual function (27,28). It was seen in the literature that other studies based on the Ex-PLISSIT model were conducted in different sample groups such as Multiple Sclerosis, Systemic Lupus Erythematosus and postpartum women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are not enough studies investigating the effect of counseling based on the Ex-PLISSIT model on primigravidas, it may be recommended to increase studies on this subject. Counseling based on the PLISSIT model, which is a similar model in pregnant women, was effective in improving sexual function (27,28). It was seen in the literature that other studies based on the Ex-PLISSIT model were conducted in different sample groups such as Multiple Sclerosis, Systemic Lupus Erythematosus and postpartum women.…”
Section: Discussionmentioning
confidence: 99%
“…total of 62 primigravidas participated in this study (Intervention group: 32, Control group: 30). The mean age of the intervention group was 27.50 (SD=3.75; range 17-34), and the mean age of the control group was 27.00 (SD=4.28; range[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The individual characteristics, sexual characteristics, thoughts and knowledge levels of the primigravidas participating in the study were similar, and no statistically significant difference was found between the groups (p>.05) (Table…”
mentioning
confidence: 99%